Современная школа: состояние тупика или движение вперед - Алламуратова, Г.Ж (SCIENCE and SOCIETY, 2020)
The article raises the problem of young generation‘s disinterest in reading books. The article describes the actual errors in texbooks on the Russian literature. A suggestion is given about the reasonableness in the choice of literary texts for inclusion in the school curricu- lum.
Keywords: education; fiction; young generation; professionalism; competence; academic knowledge; accessibility